Inhibition by Anandamide of 6-Hydroxydopamine-Induced Cell Death in PC12 Cells - Katarzyna Mnich; David P. Finn; Eilis Dowd; Adrienne M. Gorman (International Journal of Cell Biology)
6-hydroxydopamine (6-OHDA) is a selective neurotoxin that is widely used to investigate cell death and protective strategies in models of Parkinson's disease. Here, we investigated the effects of the endogenous cannabinoid, anandamide, on 6-OHDA-induced toxicity in rat adrenal phaeochromocytoma PC12 cells. Morphological analysis and caspase-3 activity assay revealed that anandamide inhibited 6-OHDA-induced apoptosis. The protection was not affected by antagonists of either cannabinoid receptors (CB1 or CB2) or the vanilloid receptor TRPV1. Anandamide-dependent protection was reduced by pretreatment with LY294002 (inhibitor of phosphatidylinositol 3-kinase, PI3K) and unaffected by U0126 (inhibitor of extracellularly-regulated kinase). Interestingly, phosphorylation of c-Jun-NH2-terminal kinase (JNK) in cells exposed to 6-OHDA was strongly reduced by anandamide pre-treatment. Furthermore, 6-OHDA induced c-Jun activation and increased Bim expression, both of which were inhibited by anandamide. Together, these data demonstrate antiapoptotic effects of anandamide and also suggest a role for activation of PI3K and inhibition of JNK signalling in anandamide-mediated protection against 6-OHDA.